The Antepartum Assessment of Fetal Well-being - Meier, Paul R. (1983)
Modern obstetrics is concerned with the health and well-being of both the mother and the unborn child. During the first two thirds of this century there was a pronounced decrease in maternal mortality and morbidity related to pregnancy. More recently, using the techniques of amniocentesis, antepartum fetal heart rate testing and ultrasound, obstetricians have been able to more accurately assess the health of a fetus. This knowledge has resulted in decreased perinatal mortality and morbidity and, when rigorously applied, a decrease in fetal loss.